Pengembangan Sistem Aplikasi Pendeteksi Long Method Smell Berdasarkan Refactoring Filtering Metrics - Habridio Kurniawan Putra; Bayu Priyambadha; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In developing or changing a software, it is necessary to observe the maintainability so that the software does not have low maintainability. Low maintainability can make the software difficult to understand, expensive to repair and develop or change in the future. One of the causes of low maintainability is code smell. Not all developers have enough knowledge about code smell, even though they understand about it, it is uncertain if they can necessarily find a solution that must be taken to overcome the code smell or not. The long method smell detection system has a feature to help developers detect it, and effective methods and refactoring methods that can be done from java source code so that it can reduce the effort of developers to overcome code smell, especially long methods. This system developed based on Refactoring Filtering Metrics (RFM), which calculates switch, edge, node, def, c-use, p-use and complexity of condition values. The RFM value used as the basis for detecting the long method smell using Refactoring Filtering Condition. This system has been tested by the Whitebox method and validation testing using the Blackbox method. This system can operate detection in less than 10 seconds and has a detection accuracy of 100 percent.